2022
DOI: 10.1017/s1352465822000157
|View full text |Cite
|
Sign up to set email alerts
|

Online Support and Intervention (OSI) for child anxiety: a case series within routine clinical practice

Abstract: Background: Online treatments for child anxiety offer a potentially cost-effective and non-stigmatizing means to widen access to evidence-based treatments and meet the increasing demand on services; however, uptake in routine clinical practice remains a challenge. This study conducted an initial evaluation of the clinical effectiveness, feasibility and acceptability of OSI (Online Support and Intervention for child anxiety) within clinical practice. OSI is a co-designed online therapist-supported, parent-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Furthermore, as also found by Hill, Chessell, et al. ( 2022 ), improvements were particularly large on the Goal Based Outcome measure, which is encouraging given that such idiographic outcome measures may be more sensitive to change than standardised outcome measures (Edbrooke‐Childs, Jacob, Law, Deighton, & Wolpert, 2015 ). In addition, despite the relatively low baseline scores among this early intervention sample, rates of reliable change and reliable deterioration compare favourably to those found in a recent meta‐analysis of outcomes in routine clinical practice in specialist mental health services (Bear, Edbrooke‐Childs, Norton, Krause, & Wolpert, 2020 ) although notably that study included children and adolescents whereas our study only included preadolescent children.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Furthermore, as also found by Hill, Chessell, et al. ( 2022 ), improvements were particularly large on the Goal Based Outcome measure, which is encouraging given that such idiographic outcome measures may be more sensitive to change than standardised outcome measures (Edbrooke‐Childs, Jacob, Law, Deighton, & Wolpert, 2015 ). In addition, despite the relatively low baseline scores among this early intervention sample, rates of reliable change and reliable deterioration compare favourably to those found in a recent meta‐analysis of outcomes in routine clinical practice in specialist mental health services (Bear, Edbrooke‐Childs, Norton, Krause, & Wolpert, 2020 ) although notably that study included children and adolescents whereas our study only included preadolescent children.…”
Section: Discussionsupporting
confidence: 74%
“…Unsurprisingly, given that this study aimed to evaluate early intervention, some effect sizes from the start to the end of treatment were somewhat smaller than in a previous evaluation of OSI that was conducted within a clinical setting (e.g., CORS pre to follow‐up here d = 0.84 compared to 0.96 in Hill, Chessell, et al. ( 2022 )). However, the improvements seen were nonetheless in keeping with those found in trials of far more intensive interventions for child anxiety disorders (e.g.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In this study with parents of 3-to 6-year-olds, although the online treatment was superior to waitlist the outcomes were relatively modest (see Table 1), but the authors concluded that 'given that the program : : : was not tailored specifically for parents of children in this age group and was somewhat makeshift in nature, the positive results obtained are particularly promising' (Donovan and March, 2014). Further promising evidence that an online approach may be a feasible, efficient and acceptable approach that is associated with good outcomes comes from a recent clinical case series in which we examined routinely captured outcome measures from a new online parent-led CBT intervention that was designed in collaboration with parents, children and clinicians (Hill et al, 2021).…”
Section: Sho Okawa Japanmentioning
confidence: 99%